"…Прийшов Святослав у пороги…” - Шаповалов, Г. (Княжа доба: історія і культура, 2014)
Розглядається питання про місце поховання князя Святослава після його загибелі на дніпрових порогах у 972 р. Публікуються матеріали досліджень “Вознесенського скарбу”, які знайшла Дніпрогесівська археологічна експедиція у 1930 р. На підставі новітніх даних запропонована інтерпретація цього унікального для Східної Європи княжого поховання-спалення як могили князя Святослава неподалік літописної Крарійської переправи на Вознесенській гірці. The article discusses the issue of the burial place of the prince Sviatoslav after his death near the Dnieper rapids in 972 A.D. It introduces into circulation materials of research of Voznesenivka treasure from nearby Dnieper Hydroelectric Station, excavated by the archaeological expedition in 1930. Based on new facts it off ers an innovative interpretation of this unique for Eastern Europe princely cremation burial site situated on the Voznesenivka hill as prince Sviatoslav grave near the ford of Krarion mentioned in the chronicles.